2005
DOI: 10.14411/eje.2005.057
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sampling plan for Myzus persicae (Hemiptera: Aphidoidea) and its predator Macrolophus costalis (Hemiptera: Miridae) on tobacco

Abstract: Abstract.A tobacco field in Greece was sampled during the 2001 and 2002 growing seasons to assess the seasonal trends in densities and spatial distributions of the aphid Myzus persicae (Sulzer) and its predatory mirid Macrolophus costalis (Fieber). On repeated occasions between June (just after the transplantation) and September (just before harvest), 20 tobacco leaves (10 from the upper and 10 from the lower plant part) were taken from randomly chosen plants. These leaves were sampled for aphids and mirids. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…This result corroborates the previous finding by Eliot & Kieckhefer (1987), who showed that Taylor's Power Law showed the spatial distribution of S. avenae, Rhopalosiphum padi, R. maidis and Schizaphis graminum better than Iwao. In addition, other results similar to ours were reported by previous studies (Dean & Luring, 1970;Feng & Nowierski, 1992;Burgio et al, 1995;Elliot & Kieckhefer, 1987;Athanassiou et al, 2005;Kavallieratos et al, 2002Kavallieratos et al, , 2005Fievet et al, 2007;Tomanovic et al, 2008a;Afshari & Dastranj, 2010), on other aphid species, S. avenae, R. padi, R. maidis and Schizaphis graminum, Metopolophium dirhodum, D. noxia and Myzus persicae.…”
Section: Discussionsupporting
confidence: 90%
“…This result corroborates the previous finding by Eliot & Kieckhefer (1987), who showed that Taylor's Power Law showed the spatial distribution of S. avenae, Rhopalosiphum padi, R. maidis and Schizaphis graminum better than Iwao. In addition, other results similar to ours were reported by previous studies (Dean & Luring, 1970;Feng & Nowierski, 1992;Burgio et al, 1995;Elliot & Kieckhefer, 1987;Athanassiou et al, 2005;Kavallieratos et al, 2002Kavallieratos et al, , 2005Fievet et al, 2007;Tomanovic et al, 2008a;Afshari & Dastranj, 2010), on other aphid species, S. avenae, R. padi, R. maidis and Schizaphis graminum, Metopolophium dirhodum, D. noxia and Myzus persicae.…”
Section: Discussionsupporting
confidence: 90%
“…Feeding location has been reported to influence both fitness as well as natural‐enemy recruitment for herbivorous arthropods in other cultivated plant systems including chili (Idris & Roff, ), cotton (Griogolli et al., ), alfalfa (Berberet et al., ), tobacco (Athanassiou et al., ; Kavallieratos et al., ), sunflowers (Pekar, ), and other brassica crops, including Brassica nigra (L.) W.D.J. Koch (Smallegange et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Presence-absence and enumerative sampling plans have been developed for various aphids and their predators (Feng et al 1993;Trumper and Gyenge 1998;Hodgson et al 2004;Athanassiou et al 2005), lepidopteran leafminers (Hamilton et al 2004), whiteflies (Naranjo et al 1996), mites (Nachman 1984; , among others. Sampling plans for estimating parasitized aphid densities are very important in order to evaluate the mortality caused by parasitoids; however, sampling plans for estimating mummified aphids' density are not very common (Giles et al 2003).…”
Section: Discussionmentioning
confidence: 99%